Lithuania : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper reviews economic developments in Lithuania during 1993-96. Economic growth resumed in 1994 and gained further momentum in 1995; real GDP increased by an estimated 3 percent in 1995. Growth in 1995 was driven by the industrial sector, while agriculture performed poorly. The immediate effects of the banking problems on economic activity, and on other macroeconomic developments, have been limited. Data on industrial production and retail trade indicate continued growth in the first part of 1996.